Determinants of pollution abatement and control expenditure in Romania: A multilevel analysis - Guglielmo Maria Caporale; Christophe Rault; Robert Sova; Anamaria Sova (Center for Economic Studies and ifo Institute (CESifo), 2010)
The transition process in Central and Eastern Europe was associated with growing environmental awareness. This paper analyses the determinants of Pollution Abatement and Control Expenditure (PACE) at plant level in the case of Romania using survey data and a Multilevel Regression Model (MRM). Our findings suggest that, although Romania has improved its environmental performance, formal and informal regulation are still only partially developed due to the difficulties of economic transition, and heterogeneity across regions remains considerable.
Keywords: Q52; C29; C40; 330; Pollution Abatement and Control Expenditure; transition economy; Multilevel Regression Model (MRM); Umweltmanagement; Umweltschutzkosten; Kontrolle; Systemtransformation; Rumänien